2021
DOI: 10.5781/jwj.2021.39.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Bonding Interface Degradation Characteristics of Gold-Coated Silver Wire for Semiconductor Packaging

Abstract: Gold-coated silver wire was developed to alleviate the high cost of Au wire used in semiconductor packaging. Ball-bonding and stitch-bonding techniques were used to fabricate the dummy packaging material, comprising 97.3 % Ag, 97.3% Au-Coated Ag, and 99.99 %Au wires. The wire ball shear test (BST), the wire ball pull test (BPT), and the microstructural attributes of the ultrasonic bonding interfaces were compared with the initial properties, both before and after the highly accelerated stress test (HAST), cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In terms of mechanical properties, electrical properties and bonding properties, the test results are better than those of gold wire and pure silver wire. Kim et al [35] found in their study that there was a thin Ag-Au-Al intermetallic compound layer at the ACA binding interface which prevented crack propagation, as shown in Figure 5. Moreover, Ag-Au-Al intermetallic compounds formed at the bonding interface of ACA wire hinder the Au-Al interdiffusion reaction and reduce the intermetallic diffusion.…”
Section: Coated Silver Wirementioning
confidence: 96%
“…In terms of mechanical properties, electrical properties and bonding properties, the test results are better than those of gold wire and pure silver wire. Kim et al [35] found in their study that there was a thin Ag-Au-Al intermetallic compound layer at the ACA binding interface which prevented crack propagation, as shown in Figure 5. Moreover, Ag-Au-Al intermetallic compounds formed at the bonding interface of ACA wire hinder the Au-Al interdiffusion reaction and reduce the intermetallic diffusion.…”
Section: Coated Silver Wirementioning
confidence: 96%